Cloning and purification of a unique lysozyme produced by Bacillus phage phi 29. - Saedi, M S (1987)
A DNA fragment of the bacteriophage phi 29 chromosome, encoding the entire sequence of phi 29 gene 15, has been cloned into the Escherichia coli expression vector pPLc245 under the control of the phage lambda major leftward promoter, PL. Upon heat induction, a protein with an apparent molecular mass of 26 kDa was overproduced. The molecular mass of this protein corresponds to the 28 kDa predicted for the product of gene 15 from its nucleotide sequence. The overproduced protein has been purified to near homogeneity and confirmed to be the product of gene 15 by amino acid sequence analysis of its N terminus. The purified product of gene 15 has a lysozyme activity similar to other phage-type lysozymes: products of phage T4 gene e and of phage P22 gene 19. However, to our knowledge phi 29 lysozyme is structurally unique among the phage-type lysozymes.